Book reviews: Miroslav N. Jovanovic – Evolutionary Economic Geography. Location of Production in the European Union - Popescu, Raluca G. (Annals of Spiru Haret University. Economic Series, 2011)
The book tries to answer the problem of locating production of a company in the geographic space analyzing what determines productivity differences between regions using the theory of evolutionary economic geography. Evolutionary economics studies “the origin, change, direction and speed in the spatial distribution and organization of as well as production and consumption in a certain period of time.” The studied problem is relevant in order to know not only what will be the future location of jobs, their quality and quantity but also where will take place the maximization of profits, the collection of taxes, the public spending, etc.